2018
DOI: 10.3390/brainsci8020024
|View full text |Cite
|
Sign up to set email alerts
|

Consonant and Vowel Processing in Word Form Segmentation: An Infant ERP Study

Abstract: Segmentation skill and the preferential processing of consonants (C-bias) develop during the second half of the first year of life and it has been proposed that these facilitate language acquisition. We used Event-related brain potentials (ERPs) to investigate the neural bases of early word form segmentation, and of the early processing of onset consonants, medial vowels, and coda consonants, exploring how differences in these early skills might be related to later language outcomes. Our results with French-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 50 publications
(138 reference statements)
3
27
5
Order By: Relevance
“…Based on previous evidence from word segmentation (Nishibayashi & Nazzi, 2016; Von Holzen et al, 2018), we may expect 8‐month‐olds to show a consonant bias during own‐name recognition. However, word form segmentation only requires the short‐term retention of a word form, whereas word form recognition requires the long‐term maintenance of a word form.…”
Section: Experiments 1:5‐ and 8‐month‐oldsmentioning
confidence: 90%
See 3 more Smart Citations
“…Based on previous evidence from word segmentation (Nishibayashi & Nazzi, 2016; Von Holzen et al, 2018), we may expect 8‐month‐olds to show a consonant bias during own‐name recognition. However, word form segmentation only requires the short‐term retention of a word form, whereas word form recognition requires the long‐term maintenance of a word form.…”
Section: Experiments 1:5‐ and 8‐month‐oldsmentioning
confidence: 90%
“…Finally, to capture the developmental consequences of individual variation in the emergence of the consonant bias, we sent follow‐up vocabulary questionnaires to the 8‐month‐old infant participants when they were 13, 16, and 24 months of age. Sensitivity to both vMPs and cMPs in word segmentation at 8 months has been found to predict growth in word production over these ages (Von Holzen et al, 2018). In the current study, however, we measure the preference for consonant compared with vowel information, which may provide a more accurate assessment of whether consonant bias emergence is related to later vocabulary outcomes.…”
Section: Experiments 1:5‐ and 8‐month‐oldsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding links between mechanisms of word segmentation and individual variability is important, because many researchers have shown that performance in speech segmentation tasks is highly predictive of later vocabulary learning (Junge & Cutler, 2014;Newman, Ratner, Jusczyk, Jusczyk, & Dow, 2006;Singh, Steven Reznick, & Xuehua, 2012;Von Holzen, Nishibayashi, & Nazzi, 2018).…”
Section: Individual Variability In Infants' Speech Environmentmentioning
confidence: 99%